Novel Harmonic Distortion Prediction Methods for Meshed Transmission Grids with Large Amount of Underground Cables - Vladislav Akhmatov; Bjarne Søndergaard Bukh; Chris Liberty Skovgaard; Bjarne Christian Gellert (Energies, 2023)
The tremendous and fast green transition in Denmark has initiated the large-scale grid-integration of renewable energy sources, electrification of energy consumption, and establishment of PtX and Energy Islands, setting goals for transmission grid development—such as the establishment of new connections—and for grid reconstruction—such as the extensive substitution of overhead lines (OHLs) with underground cables (UGCs). The share of UGCs in the Danish transmission grid is increasing. Presence of UGC has resulted in that resonances of the harmonic impedance characteristics of the transmission grid are brought within the harmonic order range coinciding with the harmonic emission sources and causing systemwide increase of the harmonic voltage distortion in the 400 kV transmission grid. The transformation of the 400 kV transmission grid has given rise to the need to predict harmonic voltage distortion using simulation models to secure an adequate power quality and support investment decisions and harmonic mitigation for the grid stage, which has not yet been established and which differs from the present grid. This paper presents the experiences of Energinet, the Transmission System Operator (TSO) in Denmark, with harmonic distortion in the Danish transmission grid due to the establishment of 400 kV UGCs, and the development of measurement-validated methods for harmonic distortion simulation and prediction. The paper also presents ongoing developments within, and research addressing, the prediction of harmonic distortion in meshed grids; for example, it explores where and how an analytical approach can replace observational studies with many numerical simulations. The methods shall make it possible to predict whether, where in the transmission grid, and for which harmonic orders connections that have not yet been commissioned may cause the violation of the planning levels, and which mitigations are necessary for bringing the harmonic distortion below the planning levels with respect to a given margin.